(untitled) (Docentes 2.0 Journal, 2024)
Yacon is a tuber cultivated in America in the warm and temperate Andean regions, in countries such as Peru and Bolivia, for more than a millennium. Yacon has been considered a superfood for its properties, its satiety effect, its richness in micronutrients, highlighting its sweet taste, and being low in calories at the same time. For this reason and by means of this project, we are trying to promote a company that produces and commercializes Yacon products. For this task, the study was carried out in the 18th district of the city of La Paz, Bolivia, and could expand to other population sectors and adapt in the best way to the target place. The project aims to start with healthy chips as substitutes for other chips and snacks with low nutritional value, and it also seeks to attract consumers who are interested in improving their appearance and health, people with diabetes, overweight, osteoporosis, cancer, and fitness problems, as well as ordinary people looking for healthier consumption alternatives. The project will be developed by using skillful administrative strategies to manage the company, with a strong focus on marketing. It is also intended to offer quality flakes that are attractive and have a pleasant taste; and at the same time, to promote the development, through sustainable growth, of the producing communities, which have a low socioeconomic level and limited development.